Factors Associated with Chest Tube Placement in Blunt Trauma Patients with an Occult Pneumothorax - Michael Paplawski; Swapna Munnangi; Jody C. Digiacomo; Edwin Gonzalez; Ashley Modica; Shawndeep S. Tung; Catherine Ko (Critical Care Research and Practice)
Background. An occult pneumothorax is identified by computed tomography but not visualized by a plain film chest X-ray. The optimal management remains unclear. Methods. A retrospective review of an urban level I trauma center’s trauma registry was conducted to identify patients with occult pneumothorax over a 2-year period. Factors predictive of chest tube placement were identified using univariate and multivariate logistic regression analysis. Results. A total of 131 patients were identified, of whom 100 were managed expectantly with an initial period of observation. Ultimately, 42 (32.0%) patients received chest tubes and 89 did not. The patients who received chest tubes had larger pneumothoraces at initial assessment, a higher incidence of rib fractures, and an increased average number of rib fractures, of which significantly more were displaced. Conclusions. Displaced rib fractures and moderate-sized pneumothoraces are significant factors associated with chest tube placement in a victim of blunt trauma with occult pneumothorax. The optimal timing for the first follow-up chest X-ray remains unclear.